Electronic structure, magnetic ordering and X-ray magnetic circular dichroism in La₁₋xPrxCo₂P₂ phosphides - Bekenov, L.V.; Moklyak, S.V.; Antonov, V.N. (Condensed Matter Physics, 2015)
The electronic structure and magnetic ordering in La₁₋xPrxCo₂P₂ (x=0, 0.25, and 1) phosphides have been studied theoretically using the fully relativistic spin-polarized Dirac linear muffin-tin orbital (LMTO) band-structure method. The X-ray absorption and X-ray magnetic circular dichroism spectra at the Co L₂,₃ and Pr M₄,₅ edges have been investigated theoretically within the framework of the LSDA+U method. The core-hole effect in the final state as well as the effects of the electric quadrupole E₂ and magnetic dipole M₁ transitions have been investigated. Good agreement with experimental measurements has been found. На основi зонних розрахункiв повнiстю релятивiстським спiн-поляризованим лiнiйним методом МТорбiталей (ЛМТО) теоретично вивченi електронна структура i магнiтне впорядкування у фосфiдах La₁₋xPrxCo₂P₂ (x = 0,0.25, та 1). В рамках методу LSDA+U теоретично дослiдженi рентгенiвськi спектри поглинання та спектри рентгенiвського циркулярного дихроїзму на краях поглинання CoL₂,₃ i PrM₄,₅. Вивчено вплив остовної дiрки в кiнцевому станi, а також електричних квадрупольних E₂ i магнiтних дипольних M₁ переходiв. Отримано добре узгодження з експериментальними результатами.